If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(1-4x)-4(-4x-5)=5
We move all terms to the left:
5(1-4x)-4(-4x-5)-(5)=0
We add all the numbers together, and all the variables
5(-4x+1)-4(-4x-5)-5=0
We multiply parentheses
-20x+16x+5+20-5=0
We add all the numbers together, and all the variables
-4x+20=0
We move all terms containing x to the left, all other terms to the right
-4x=-20
x=-20/-4
x=+5
| 13+4b=5 | | 17k=16k+3 | | -2x=-2(3x-8) | | -8=16-7y | | F=2c-32 | | -9f-19=19-11f | | -3(4t-2)+2t=7t-2 | | 8x+9=12+8x | | |4-5x/6|=20 | | x*0.05=775 | | 2-10m+7=(-3)-11m | | 6x-10+10x-10=180 | | -3z-7z=-10 | | 2-10m+7=(-3)-11 | | 2x-6x=8x-12 | | 9x-6=4x-19 | | 9z+9=54 | | 6-8s=(-6)-6s | | -5(-2-6x)=-15+5x | | 6x-2+2x-10=180 | | 8y+4=11y–17 | | x=37+1/3 | | -8+3b=4+5b | | -1+4w-5=5w-9 | | x*0.05=750 | | -13x12=-156 | | 7{x-2}=7x+14 | | 2/5x+1/5x-2=1 | | (-2)-z=(-2z) | | x*0.03=750 | | 9(w-5)-7w=5(3w-2) | | 3x–5=x–9 |